Investigation on the performance and emission characteristics of steam packaged boiler using diesel-cooking oil blended - Hassan, S. (2013)
The performance and gas emission characteristics of steam packaged boiler using diesel-palm cooking oil blended as fuel has been investigated and evaluated. In this study, the diesel-cooking oil blends at various volume ratio were used to fueled the steam packaged boiler. The characterizations of the blended diesel-cooking oil were studied in terms of the viscosity, calorific value and density at various volume ratio from 10/90 to 90/10 of diesel-palm cooking oil blending ratio. Experiments were carried out at low and high burner setting to raised the steam to the normal operating pressure. Based on the results obtained, by using the diesel-palm cooking oil blends, a comparable performance of boiler as compared to pure diesel was observed. However, there is a great reduction in nitrogen oxide, nitrogen dioxide as well as sulfur oxide emissions. Therefore, the experimental results indicate that using an alternative fuel in the boiler is another an effective way on reduction the gas emissions and at the same time maintained the performance of the boiler operation. Â© 2013 IEEE.